2007
DOI: 10.1165/rcmb.2006-0160oc
|View full text |Cite
|
Sign up to set email alerts
|

Der p, IL-4, and TGF-β Cooperatively Induce EGFR-Dependent TARC Expression in Airway Epithelium

Abstract: Thymus and Activation-Regulated Chemokine (TARC) may be critical in Th2 cell recruitment in allergic inflammation; however, the mechanisms of allergen-induced TARC release are unclear. Since airway epithelium is the first line of defense to inhaled allergens, we questioned whether house dust mite allergen (Der p) can induce TARC expression in bronchial epithelial cells, how this is regulated at the molecular level, and if micro-environmental cytokines augment this effect. We examined the effects of Der p and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 50 publications
3
53
0
Order By: Relevance
“…EGFR signaling is activated by asthma-related cytokines and inflammation (40). House dust mite allergen (Der p) increases the secretion of thymus and activation-regulated chemokine in an EGFR-dependent manner, resulting in allergic inflammation (41). It is probable that cross-talk between EGFR and Fc⑀RI is necessary for allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling is activated by asthma-related cytokines and inflammation (40). House dust mite allergen (Der p) increases the secretion of thymus and activation-regulated chemokine in an EGFR-dependent manner, resulting in allergic inflammation (41). It is probable that cross-talk between EGFR and Fc⑀RI is necessary for allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Airway epithelial cells induce migration of Th1 cells into mucosae via production of the CXCR3 ligands, CXCL9 (Mig), CXCL10 (IP-10) and CXCL11 (I-TAC), and induce migration of Th2 cells via production of the CCR8 ligand CCL1 (I-309) and the CCR4 ligands CCL17 (TARC) and CCL22 (MDC) (Figure 1) [42][43][44][45][46][47]. CXCR3 is expressed on activated T cells, predominantly of the Th1 phenotype, as well as on NK cells and a subset of circulating memory CD4 + and CD8 + T cells.…”
Section: Interaction Of Epithelial Cells With T Cellsmentioning
confidence: 99%
“…CCR4, a receptor for the epithelial products CCL17 and CCL22, is also expressed on Th2 cells. CCL17 production is induced by IL-4, IL-13, TGF-β and the house dust mite allergen Der p in airway epithelial cells [46,47]. In addition, synergistic induction of CCL17 is induced by the combination of TNF with either Th2 cytokines, TGF-β or Der p antigen.…”
Section: Interaction Of Epithelial Cells With T Cellsmentioning
confidence: 99%
“…Uto et al reported that 6-MSITC inhibited MAPK signaling pathways in inflammation (19,27). It has also been reported that expressions of TARC and eotaxin are controlled via MAPK signaling pathways (28,29). 6-MSITC might adjust chemical mediators through MAPK signaling pathways.…”
Section: Effects Of Wasabi Rhizome Extract On the Plasma Components Amentioning
confidence: 99%